(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
In order to develop floriculture in our republic, especially in the Namangan region, in order to grow tulip bulbs with high quality and cheap, and raise it to an industrial level, research work is being carried out in developed foreign countries, planting tulip bulbs has been studied and based on analysis units for planting tulip bulbs with a simple design and low cost, a method for planting tulip bulbs and a design diagram of the unit that implements it have been developed.